„Польскость” и „русскость” в мифологическом зеркале. К вопросу о современном публичном дискурсе - Korzeniewska-Berczyńska, Joanna (Acta Polono-Ruthenica, 2006)
The discourse involves a number of prominent thinkers who express their opinions in quality newspapers and magazines. The concept of Polish national character consists mainly of historical myths, and the dramatically transforming Russian character is to a great extent an absolute rejection of the Sowiet past and an equally approval of the Tsar period.In her analysis, the author identifies the characteristic features of both Polish and Russian national character. The issue can be perceived as a proof of seeking the national identity but also as some camouflage supposed to divert attention from real social problems.